Archéologie du Cap Espenberg où la question du Birnirk et de l’origine du Thulé dans le nord-ouest de l’Alaska - Alix, Claire; Mason, Owen K.; Bigelow, Nancy H.; Anderson, Shelby L.; Rasic, Jeffrey; Hoffecker, John F. (Les Nouvelles de l'archéologie, 2015)
Cape Espenberg is a sandy spit on the Chukchi Sea coast in northwestern Alaska, containing the remains of 4000 years of human occupation and climatic change. Archaeological and paleo-ecological research since 2009 as part of a large pluridisciplinary project provides new data on settlement chronology for the last thousand year of occupation and documents the emergence of the Thule culture which is directly ancestral to today’s Inuit/Inupiat in a context of increased storminess during the Little Ice Age. At the same time, this research raises the question of the nature of the Birnirk occupation identified on the low E-6 dune ridge, site KTZ-304, an archaeological complex which contributes to the emergence of the Thule culture between the 12th and 13th AD. This Birnirk mound at Cape Espenberg resembles in many aspects the type side named Birnirk in north Alaska (Barrow region). The excavation of house F12 uncovered a multi-room structure with overlain occupation levels and produced a collection of remains showing real architectural differences, signs of long distance raw material and object circulation and of mobility. All these elements suggest newcomers possibly of Chukotka origin and provides the opportunity to revisit an old research question in Arctic archaeology, that of the origin of Birnirk culture on the Alaska coast. Le cap Espenberg est une flèche littorale au large de la mer des Tchouktches dans le nord-ouest de l’Alaska contenant les vestiges de 4000 ans d’occupations humaines et de changements climatiques. Les recherches archéologiques et paléo-environnementales, menées depuis 2009 dans le cadre d’un projet pluridisciplinaire, apportent des informations nouvelles sur la chronologie des occupations du dernier millénaire et documentent l’émergence de la culture thuléenne directement antérieure et ancestrale aux Inuit/Inupiat d’aujourd’hui, dans un contexte d’intensification des conditions cycloniques, contemporain du petit âge glaciaire. Parallèlement, ces recherches posent la question de la nature ...